Karakteristik Pasien Rinitis Alergi dengan Hasil Uji Cukit Kulit Positif yang Berobat di Poliklinik THT-KL Rumah Sakit Umum Daerah Zainoel Abidin Banda Aceh - T.R, T. Husni; Murzalina, Cut; Elvia, Elvia; Alia, Dina; Razali, Rezania; Annisa, Siti Nur; Putra, Teuku Romi Imansyah; Farhana, Rika (Jurnal Penyakit Dalam Indonesia, 2024)
Introduction. Allergic rhinitis is an inflammatory disease mediated by IgE in the nasal mucosa, resulting from allergen sensitization and causing various clinical symptoms. The skin prick test is the primary diagnostic technique used to detect specific IgE antibodies against allergenic proteins and peptides. The incidence of allergic rhinitis in Indonesia ranges from approximately 1.5% to 12.4% and increases every year. This study aims to determine the characteristics of allergic rhinitis sufferers with positive skin prick test results who received treatment at the ENT outpatient service of Zainoel Abidin Regional General Hospital (RSUDZA) Banda Aceh from January 2019 to March 2020. Methods. This was a retrospective descriptive study with a cross-sectional design that utilized secondary data from patient medical records. The samples were collected using the total sampling technique, encompassing a total of 62 patients in this study. Results. This study revealed that allergic rhinitis sufferers with positive skin prick test results were predominantly in the age group 17-25 years (27.4%), female (69.4%), and from Banda Aceh (56.5%). Most of the rhinitis patients were students (41.9%), with the highest level of education being high school (43.5%). Allergic rhinitis is frequently caused by house dust mites (24.2%) as inhalant allergens and shrimp (26.3%) as ingested allergens. Most allergic rhinitis patients who visited complained most frequently of sneezing more than five times (26.3%). Conclusions. This study concluded that the characteristics of allergic rhinitis sufferers with positive skin prick test results in RSUDZA are predominantly in the late adolescent age group (17-25 years), female, with house dust mites and shrimp as the main allergens, and the most common clinical symptom is sneezing more than 5 times.